Secondary intraocular lens implantation following infantile cataract surgery: intraoperative indications, postoperative outcomes - Wood, K S (Eye (Lond), 2016)
PURPOSE: The purpose of this study was to determine the long-term complications and outcomes of secondary intraocular lens (IOL) implantation in patients with congenital cataracts. PATIENTS AND METHODS: The medical records of children operated for secondary IOL implantation surgery between 2000 and 2014 were retrospectively reviewed. Those who had undergone their initial congenital cataract surgery before 7 months of age were included and were analyzed for intra- and postoperative factors and postoperative refractive outcomes. We focused on three complications: visual axis opacification (VAO), glaucoma, and IOL exchange after at least 1 year of follow-up. RESULTS: A total of 49 eyes of 49 patients were analyzed for intraoperative indications. Of those, 37 eyes of 37 patients had at least 1 year of follow-up and were analyzed for postoperative outcomes. The mean age at secondary implantation was 55.2±21.6 months. At secondary implantation, 69.4% of eyes were implanted in the capsular bag, 28.6% in the sulcus, and 2.0% that were angle-supported. There was no significant correlation between the site of secondary IOL implantation and age at implantation (P=0.216). The mean follow-up after implantation was 57.6±33.6 months. The rate of VAO was 5.4%, the rate of glaucoma occurring after secondary implantation was 16.2%, and the rate of IOL exchange was 2.7%. The median visual acuity at final follow-up was 20/40. For patients with unilateral cataracts it was 20/60 and for bilateral patients it was 20/30. CONCLUSIONS: The secondary IOL implantation in children is a relatively safe procedure associated with low rates of postoperative complications. Visual outcomes are acceptable and are better for bilateral patients than for unilateral patients.